2011
DOI: 10.1111/j.1365-2486.2011.02532.x
|View full text |Cite
|
Sign up to set email alerts
|

A potential tool to mitigate the impacts of climate change to the caribbean leatherback sea turtle

Abstract: It is now well understood that climate change has the potential to dramatically affect biodiversity, with effects on spatio-temporal distribution patterns, trophic relationships and survivorship. In the marine turtles, sex is determined by incubation temperature, such that warming temperatures could lead to a higher production of female hatchlings. By measuring nest temperature, and using a model to relate the incubation temperature to sex ratio, we estimate that Caribbean Colombian leatherback sea turtles cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 102 publications
7
74
0
1
Order By: Relevance
“…Due in large part to the endangered status of sea turtles, direct assessment of clutch sex ratios through histological examination of the gonads is not often possible, and sand temperatures are commonly used as indirect estimators of sex ratio (e.g. Oz et al 2004, Booth & Freeman 2006, Patino-Martinez et al 2012. Recent work on hawksbills has demonstrated that nest temperatures are a highly significant predictor of sex ratio in natural nests (Mrosovsky et al 2009).…”
mentioning
confidence: 99%
“…Due in large part to the endangered status of sea turtles, direct assessment of clutch sex ratios through histological examination of the gonads is not often possible, and sand temperatures are commonly used as indirect estimators of sex ratio (e.g. Oz et al 2004, Booth & Freeman 2006, Patino-Martinez et al 2012. Recent work on hawksbills has demonstrated that nest temperatures are a highly significant predictor of sex ratio in natural nests (Mrosovsky et al 2009).…”
mentioning
confidence: 99%
“…Exposure to contaminants could change the production of hormones such as estradiol or vitellogenin in females affecting egg production (Rie et al, 2005), and can also alter hormone production, sperm quality and activity in males (Van Look Kime, 2003;Ferber, 2005;De Andrés et al, 2016). Moreover, the male population of sea turtles could be severely threatened by problems like male selective fishing activities and alteration of sex ratio in hatchlings due to global warming (Patino-Martinez et al, 2012;AbellaPérez et al, 2016). For instance, all sea turtle species have been classified as endangered across their range, and in spite of being an illegal practice, sea turtle meat consumption is a deeply-rooted traditional activity in most nesting areas of the world (Klemens et al, 2000;Lutz et al, 2003).…”
mentioning
confidence: 99%
“…Instead, the conservation of leatherback turtles, especially in the Pacific Ocean where populations are already severely depleted (Spotila et al 2000, Tapilatu et al 2013, may have to rely on additional proactive measures to reduce incubation temperatures for eggs through direct manipulation of environmental conditions, e.g. watering or shading nests (Patino-Martinez et al 2012). …”
Section: Conservation Implicationsmentioning
confidence: 99%